Livestock farmer-reported knowledge and attitudes regarding agroforestry planning and management - De-Sousa, Karolini Tenffen; Wright, Melanie; Cárdenas, Laura M.; Deniz, Matheus [UNESP]; Dittrich, João Ricardo; Hötzel, Maria José; Enriquez-Hidalgo, Daniel (Springer Nature, 2025)
This study aimed to explore the knowledge and attitudes of livestock farmers from the United Kingdom regarding agroforestry planning and management issues. The farmers (n = 48) answered an online survey with demographic, open, closed and Likert scale questions. Almost half of the participants said they need more information to successfully plan and manage an agroforestry system, and self-reported low knowledge on management practices related to trees. Participants stated they did not expect to receive technical support from governmental agencies to maintain the agroforestry area. However, they would like to improve their knowledge through field days, courses, and Internet sources. Benefits to the environment, animals and farm profitability were considered central to successful agroforestry systems. In conclusion, participants cannot successfully plan and manage agroforestry, but they are willing to improve their knowledge and skills.
Keywords: Expertise; Farm owner; Integrated systems; Opinion; Silvopasture